The EFFECT OF SUPERVISION, WORK DISCIPLINE, ORGANIZATIONAL COMMITMENT AND STANDARD OPERATIONAL PROCEDURES (SOP) ON EMPLOYEE PERFORMANCE AT PT QUALITECH INDOPIRANTI BANDUNG BRANCH - Firgiawati Sandra, Herlia; Permata Rahmi, Palupi; Herlina, Listri (Universitas Indonesia Membangun (Inaba), 2022)
The implementation of supervision, discipline, commitment and Standard Operating Procedures in the company can increase the quality of work that is able to manage the company well and professionally, so that in the future the company can achieve good success in advancing a company. The purpose of this study was to determine the effect of the implementation of supervision, work discipline, organizational commitment and the application of Standard Operating Procedures on the performance of employees of PT. Qualitech Indopiranti Bandung Branch either partially or simultaneously. The research method used is a quantitative method with a descriptive and verification approach. The population in this study were all employees of PT. Qualitech Indopiranti Bandung Branch as many as 40 people sampling using total sampling or sampling saturated (census). Validity test using Product Moment correlation from Pearson. While the reliability test uses Cronbach's Alpha. Data collection techniques through the distribution of questionnaires. The analysis prerequisite test includes normality test, multicollinearity test, heteroscedasticity and linearity test. The data analysis technique used is multiple regression, correlation test, and coefficient of determination. The results showed that the descriptive analysis stated that: 1). Employee performance was in a good category. 2). Supervision was in a good category. 3). Work discipline was in a good category. 4). Organizational commitment was in a good category. 5). Standard Operating Procedures was in a good category . Besides that, the results of the study show that, 6). Supervision has an effect on employee performance with a correlation value of 0.831 with a very strong relationship level. 7). Work Discipline has an effect on employee performance with a correlation value of 0.995 with a very strong relationship level. 8). Organizational commitment has an effect on employee performance with a correlation value of 0.5611 with a strong relationship level. 9). Standard Operating Procedures affect employee performance with a correlation value of 0.829 with a very strong relationship level. 10). Supervision, Work Discipline, Organizational Commitment and Standard Operating Procedures on Employee Performance have a simultaneous effect on employee performance with an influence value of 99.1%, and a very strong correlation with a correlation value of 0.995.